The upper respiratory tract microbiota of healthy adults is affected by Streptococcus pneumoniae carriage, smoking habits, and contact with children - Paulo, A. Cristina (2023)
Funding Information: This work was supported by Fundação para a Ciência e a Tecnologia (FCT), I.P., through MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020, UIDP/04612/2020) and LS4FUTURE Associated Laboratory (LA/P/0087/2020). JL and STA were supported by FCT grants UI/BD/153385/2022 and SFRH/BD/108380/2015, respectively. The funders had no role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: © 2023, BioMed Central Ltd., part of Springer Nature.